(untitled) (Research, Society and Development, 2021)
The aim of this study was to determine the yield, phytochemical prospection, content of total phenolic compounds and total flavonoids in plant extracts from leaves of the species Anacardium occidentale, popularly known as cashew. Four solvents were used for extraction: acetone PA, cyclohexane PA, ethyl alcohol 70% (v.v) and water. The samples were collected in the territory of the Federal University of Maranhão, located in São Luís – MA. Extracts were produced using maceration. The percentage yield was determined from the in natura material and the phytochemical screening of the extracts was performed using qualitative colorimetric and precipitation methods. The content of total phenolics and flavonoids was determined using the colorimetric method using Folin-Ciocalteau reagent and 5% aluminum chloride. Cashew extracts showed the following results in the quantification of total phenolics: 820 mg EAT.g-1 for the alcoholic extract, 476 mg EAT. g-1 for acetone extract PA, 280.23 mg EAT. g-1 for aqueous extract and 243.76 mg EAT. g-1 for the cyclohexane PA extract. The values ​​obtained in the analysis of flavonoid contents were: 11.89 mg EQ. g-1 for cyclohexane PA, 10.80 mg EQ. g-1 for acetone PA, 4.35 mg EQ. g-1 for 70% ethyl alcohol (v.v) and 0.915 mg EQ. g-1 for the aqueous. It was concluded that the extract with the highest total yield was cyclohexane PA, in phenolic compounds content it was the alcoholic solvent, and in flavonoid content it was the cyclohexane solvent.